Effect of stabilisation training on trunk muscle size, motor control, low back pain and player availability among elite australian rules football players. Issue 4 (27th March 2011) - Hides, J; Stanton, W; Mendis, M D; Gildea, J
Abstract : Background: Among the injuries in Australian Rules Football League (AFL), hip, thigh and groin muscle injuries are highly prevalent. The prevalence rates of injuries classified as 'trunk/back' in the AFL injury report have not decreased over the past 16 years. In addition, low back pain (LBP) is common among AFL players. Deficits within the lumbo-pelvic region such as impaired motor control, is thought to contribute to injuries. Objective: To investigate the effect of a staged stabilisation training program on trunk muscle size and motor control. Design: Randomised control trial. Setting: MRI examinations were carried out in a hospital setting, and the stabilisation training was conducted at the AFL club premises. Participants: 42 male elite players representing the training squad of an AFL club, participated in the study. Interventions: The stabilisation program involved voluntary contraction of the multifidus, transversus abdominis, and pelvic floor muscles, with real-time feedback from rehabilitative ultrasound imaging, progressed from non-weight-bearing to weight-bearing positions. Training sessions were 30 min in duration, and were conducted twice per week for 7–15 weeks. Main outcome measurements: The dependent variables were the cross-sectional areas (CSA) of the multifidus muscles, the ability to draw in the abdominal wall (CSA of the trunk, relaxed versus contracted), pain (Visual analogue scale) and player availability for competition games. Results: In the control group, multifidus muscle CSA decreased. Stabilisation training was associated with an increase in multifidus muscle CSA and an increased amount of abdominal wall draw-in. This was concomitant with a decrease in LBP and an increase in player availability. Conclusion: Alterations in muscle size and motor control can exist in highly active, elite athletes. Specific retraining during the season was effective in terms of increasing availability of players and decreasing LBP.